2012
DOI: 10.1074/jbc.m111.273854
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel Immunomodulatory Bursal-derived Pentapeptide-II (BPP-II)

Abstract: Background:The bursa of Fabricius is the acknowledged central humoral immune organ. Results: Novel bursal-derived BPP-II regulates expressions of immune-related gene and exerts immunomodulatory functions and activates p53 expression with antiproliferation on tumor cells. Conclusion: BPP-II integrates linking between humoral immunity and cell-mediated immunity, including antitumor. Significance: This might be the first sign of mechanisms involved in humoral immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…The bursa extracts of BF were sequentially separated and purified as described for soluble polypeptide from the bursal sample as described in the previous reported method [16, 17] with some modification. Briefly, the crude extracts of BF from one-month-old avian were obtained by homogenization and centrifugation at 12,000 rpm for 45 min and then ultrafiltered with molecular weight less than 1 kDa at 4°C for 48 h. The obtained sample was purified on a SinoChrom ODS-BP RP-HPLC affinity column (250 × 4.6 mm, Elite) using a linear gradient of acetonitrile (2–100%) with a DAD UV-V detector at 220 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bursa extracts of BF were sequentially separated and purified as described for soluble polypeptide from the bursal sample as described in the previous reported method [16, 17] with some modification. Briefly, the crude extracts of BF from one-month-old avian were obtained by homogenization and centrifugation at 12,000 rpm for 45 min and then ultrafiltered with molecular weight less than 1 kDa at 4°C for 48 h. The obtained sample was purified on a SinoChrom ODS-BP RP-HPLC affinity column (250 × 4.6 mm, Elite) using a linear gradient of acetonitrile (2–100%) with a DAD UV-V detector at 220 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, bursal peptide BP8 could promote colony-forming pre-B formation and regulate B cell development [13], and BP5 regulated B cell development by promoting antioxidant defense [14]. Bursal pentapeptide-II (BPP-II) and BP5 regulated various pathways and immune-related biological processes in hybridoma cells secreting monoclonal antibody especial to JEV [15, 16]. Additionally, bursal pentapeptide-I (BPP-I) inhibited tumor cell proliferation and induced p53 expression [17].…”
Section: Introductionmentioning
confidence: 99%
“…The BF contains a variety of bioactive substances, and bursin, the first peptide isolated from BF, selectively stimulated the differentiation of avian B lymphocytes precursor in vitro [ 3 5 ]. In recent years, various peptides have been isolated from BF, most of which have immunoregulatory functions [ 7 8 9 10 11 17 20 23 ]. In addition to their immune regulatory function, bursal peptides (BPs) derived from BF have exhibited other biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a central role in the proliferation and differentiation of the antibody-producing B lymphocyte lineage1. Previous studies have shown that some defined peptides sequenced from a BF extract (e.g., bursin and bursal anti-steroidogenic peptide) stimulate specific immune cell subsets2,3 isolated a new pentapeptide, bursopentin (BP5; Cys-Lys-Arg-Val-Tyr), from a BF extract. BP5 was shown to have immunomodulatory effects, including effects on T and B cells, the antioxidant stress response of macrophages, and an inhibitory effect on tumor cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on BF extracts and multiple biologically active factors and their effects on the humoral immune system in chickens and other birds2. However, the mechanisms through which these immunomodulatory peptides affect B lineage cell proliferation and antibody production in chickens is poorly understood.…”
Section: Introductionmentioning
confidence: 99%